2019
DOI: 10.21608/jhiph.2019.49272
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Indications and Determinants of Caesarean Delivery in Alexandria, Egypt

Abstract: Background: Prevalence of Caesarean delivery (CD) is increasing worldwide including Egypt. Alexandria is one of the governorates recording the highest rates in Egypt. Identifying factors associated with CD is important to plan for reduction. Objective: To identify prevalence, indications and determinants of CD in Alexandria, Egypt. Methods: This cross sectional survey was carried out in Alexandria, Egypt between July and December 2017. Target population was ever-married fertile women aged 15-49 years. Only wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The mothers with preceding birth intervals of 21–30 months are more susceptible to DCS. An investigation identifying the prevalence and determinants of CS in Alexandria, Egypt, elucidated that preceding birth intervals substantially impact the DCS among Egyptian women [ 46 ]. A systematic review and meta-analysis on CS and pregnancy interval observed the association of birth interval with DCS [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mothers with preceding birth intervals of 21–30 months are more susceptible to DCS. An investigation identifying the prevalence and determinants of CS in Alexandria, Egypt, elucidated that preceding birth intervals substantially impact the DCS among Egyptian women [ 46 ]. A systematic review and meta-analysis on CS and pregnancy interval observed the association of birth interval with DCS [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that CS rates were always higher in the rural than the urban district. One study recorded a CS rate of 70.4% in Alexandria during 2017 21 . Comparing Egypt to other parts of the world, CS rate in Egypt was 51.8%, the highest in Africa; 47.9% in Iran, 47.5% in Turkey, 38.1% in Italy, 32.8% in United States, and 33.4% in New Zealand 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Awareness assessment tool (pre/post educational program): It is a Self-Administered questionnaire that was developed by the researcher after revising relevant literature. Total number of the question were 31 questions which included questions related to different types of exercise in pregnancy (9), benefits of exercise in pregnancy (12), and contraindication of exercise in pregnancy (10)…”
Section: The Second Toolmentioning
confidence: 99%